2018
DOI: 10.1101/430876
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial and temporal inhibition of FGFR2b ligands reveals continuous requirements and novel targets in mouse inner ear morphogenesis

Abstract: Morphogenesis of the inner ear epithelium requires coordinated deployment of several signaling pathways and disruptions cause abnormalities of hearing and/or balance. The FGFR2b ligands, FGF3 and FGF10, are expressed throughout otic development and are required individually for normal morphogenesis, but their prior and redundant roles in otic placode induction complicates investigation of subsequent combinatorial functions in morphogenesis. To interrogate these roles and identify new effectors of FGF3 and FGF1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Genetic approaches to manipulate FGF signaling in vivo use mice in which ligands (FGF2, FGF7, FGF9, FGF10, and FGF18) or a constitutively activated FGFR1 can be induced to activate cell non‐autonomous or cell autonomous FGF signaling, respectively (Cilvik et al, 2013; Clark et al, 2001; Koo et al, 2018; Tichelaar et al, 2000; Volckaert et al, 2017; White et al, 2006; Whitsett et al, 2002). Similarly, induced expression of dominant‐negative FGFR1 or FGFR2b or the FGFR downstream pathway inhibitor SPRY4, allow cell non‐autonomous or cell autonomous, respectively, suppression of FGF signaling (Eckenstein et al, 2006; Parsa et al, 2008; Perl et al, 2003; Urness et al, 2018). In zebrafish, a transgenic allele encoding a dominant‐negative Fgfr1a with a fluorescent tag (fgfr1‐dn‐cargo) placed under combined Cre/lox and heat shock control allows spatiotemporal perturbation of FGF signaling (Kirchgeorg et al, 2018).…”
Section: Tools To Manipulate and Monitor Fgf Signaling In Vitro And I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic approaches to manipulate FGF signaling in vivo use mice in which ligands (FGF2, FGF7, FGF9, FGF10, and FGF18) or a constitutively activated FGFR1 can be induced to activate cell non‐autonomous or cell autonomous FGF signaling, respectively (Cilvik et al, 2013; Clark et al, 2001; Koo et al, 2018; Tichelaar et al, 2000; Volckaert et al, 2017; White et al, 2006; Whitsett et al, 2002). Similarly, induced expression of dominant‐negative FGFR1 or FGFR2b or the FGFR downstream pathway inhibitor SPRY4, allow cell non‐autonomous or cell autonomous, respectively, suppression of FGF signaling (Eckenstein et al, 2006; Parsa et al, 2008; Perl et al, 2003; Urness et al, 2018). In zebrafish, a transgenic allele encoding a dominant‐negative Fgfr1a with a fluorescent tag (fgfr1‐dn‐cargo) placed under combined Cre/lox and heat shock control allows spatiotemporal perturbation of FGF signaling (Kirchgeorg et al, 2018).…”
Section: Tools To Manipulate and Monitor Fgf Signaling In Vitro And I...mentioning
confidence: 99%
“…Mice lacking Fgf10 have a shortened and narrower cochlear duct, as well as defects in non‐sensory regions of the inner ear (Munnamalai & Fekete, 2020; Urness et al, 2015). Inhibition of FGF3 and FGF10 at the otic placode stage with a soluble FGFR2b transgene show that both ligands are required after otocyst formation for maintenance of otic neuroblasts and for patterning and proliferation of the epithelium of both the cochlear and vestibular domains (Urness et al, 2018).…”
Section: Fgf Signaling In the Brain And Sensory Organsmentioning
confidence: 99%
“…Another candidate factor for the upregulation of PAX2 is FGF signalling. FGF10 is expressed in the ventromedial part of the otocyst, which is a PAX2-positive area, and hindbrain-derived FGF3 is important for the development of the cochlea [ 43 ]. Therefore, to investigate the possible roles of FGF3 and FGF10 in otic placode induction, we started to culture Day 14 cells in the presence of FGF3/FGF10 as well as LDN and CHIR.…”
Section: Resultsmentioning
confidence: 99%
“…Mouse model studies have demonstrated the importance of FGFR2b ligands FGF3 and FGF10 in the development of the inner ear including otocyst patterning and vestibular and cochlea morphogenesis. 10 The authors demonstrate various morphological variations of the inner ear structure brought about by altering FGF3 and FGF10 expression. 10 We hypothesize that the inner ear appearances in our patient population arise from a similar embryological mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…10 The authors demonstrate various morphological variations of the inner ear structure brought about by altering FGF3 and FGF10 expression. 10 We hypothesize that the inner ear appearances in our patient population arise from a similar embryological mechanism.…”
Section: Discussionmentioning
confidence: 98%